2005
DOI: 10.1111/j.1471-4159.2004.02980.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of atorvastatin against glutamate‐induced excitotoxicity in primary cortical neurones

Abstract: Statins [3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitors] exert cholesterol-independent pleiotropic effects that include anti-thrombotic, anti-inflammatory, and antioxidative properties. Here, we examined direct protective effects of atorvastatin on neurones in different cell damage models in vitro. Primary cortical neurones were pre-treated with atorvastatin and then exposed to (i) glutamate, (ii) oxygenglucose deprivation or (iii) several apoptosis-inducing compounds. Atorvastatin signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
126
1
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(141 citation statements)
references
References 60 publications
6
126
1
8
Order By: Relevance
“…Atorvastatin attenuated the glutamate-induced increase of intracellular calcium, which was associated with a modulation of N-methyl-D-asparate (NMDA) receptor functions (Boesel et al 2005). Also it is shown that HMG-CoA reductase inhibition causes a profound reduction of neurite length, neurite loss and neuron death in undifferentiated rat cortical neurons (Schulz et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Atorvastatin attenuated the glutamate-induced increase of intracellular calcium, which was associated with a modulation of N-methyl-D-asparate (NMDA) receptor functions (Boesel et al 2005). Also it is shown that HMG-CoA reductase inhibition causes a profound reduction of neurite length, neurite loss and neuron death in undifferentiated rat cortical neurons (Schulz et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, many studies show that statins may have additional neuroprotective properties independent of their effect on cholesterol synthesis. Statins can reduce the region of focal cerebral ischemia [1] and protect cortical neurons from excitotoxity [2] . Recent studies reported that statins can preventively and therapeutically attenuate traumatic brain injury and spinal cord injury.…”
Section: Introductionmentioning
confidence: 99%
“…An in vitro study reported neuronal protection by atorvastatin in glutamate-induced toxicity [75]. Moreover, the observed neuroprotection and recovery in animal models of spinal cord injury [55] and traumatic brain injury [76][77][78] following statin treatment suggest statin-mediated neuroprotection in these animal models of brain injury.…”
Section: Statins Inhibit Axonal Lossmentioning
confidence: 96%